Investigation on Pathological Aspects, Mode of Transmission, and Tissue Tropism of Antheraea proylei Nucleopolyhedrovirus Infecting Oak Tasar Silkworm. Issue 5 (7th October 2022) - Khajje, Diksha; Devi, Sinam Subharani; Subrahmanyam, Gangavarapu; Kobayashi, Jun; Sivaprasad, Vankadara; Terenius, Olle; Ponnuvel, Kangayam M
Abstract: The temperate oak tasar silkworm, Antheraea proylei, is frequently infested with Antheraea proylei nucleopolyhedrovirus (AnprNPV) causing tiger band disease. This disease is one of the key factors that obstructs production and productivity of oak tasar sericulture. The current study aimed to investigate the pathogenicity of AnprNPV, its mode of transmission, and detection of AnprNPV in different tissues. Transmission electron micrographs of AnprNPV showed single rod-shaped bodies and occlusion derived virus (ODV) enclosed within multiple envelopes. The infecting AnprNPV displayed tissue tropism with higher copy numbers detected in the insect fat body and ovary. The virus was observed to multiply in all developmental stages of the silkworm such as egg, larva, pupa, and moth, confirming its ability to spread throughout the silkworm lifecycle. Baculovirus isolated from infected A. proylei showed cross-infectivity in other Saturniidae wild silkworm species such as Antheraea pernyi, A. frithi, and Samia ricini, widening their probable host range for infection. Baculoviruses generally display a horizontal mode of transmission, mainly through ingestion of occlusion bodies (OBs); however, the present study revealed a trans-ovum vertical mode of transmission in addition to a horizontal mode. The observations made in this study aid a detailed understanding of the tiger band disease and its causative pathogen AnprNPV, which will support future studies and disease management in oak tasar sericulture.